2002
DOI: 10.1677/joe.0.1730023
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to sustained high plasma vasopressin in water and electrolyte homeostasis in the rat transgenic for the metallothionein-vasopressin fusion gene

Abstract: Prolonged exposure of tissues to a receptor agonist often leads to adaptive changes that limit the subsequent responsiveness of the tissue to the same agonist. Recently, we have generated rats transgenic for the metallothionein I-human arginine vasopressin (AVP) fusion gene (Tg), which produced high plasma AVP with relatively preserved renal water excretion, suggesting that there might be adaptive mechanism(s) for maintaining water and electrolyte homeostasis against chronic AVP oversecretion from the earliest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Acute induction of AVP secretion combined with water loading therefore appears to cause diluting hyponatremia in Tg rats. This is supported by Yokoi et al (2002), who revealed a decrease in plasma total protein after the zinc liquid diet.…”
Section: Figuresupporting
confidence: 53%
See 1 more Smart Citation
“…Acute induction of AVP secretion combined with water loading therefore appears to cause diluting hyponatremia in Tg rats. This is supported by Yokoi et al (2002), who revealed a decrease in plasma total protein after the zinc liquid diet.…”
Section: Figuresupporting
confidence: 53%
“…The escape involves suppression of aquaporin 2 expression in the collecting duct (Ecelbarger et al 1997), associated with a decrease in V2 receptor mRNA (Murase et al 1999) and protein (Tian et al 2000). We have analyzed the precise mechanisms for such 'vasopressin tolerance' status in Tg rats (Yokoi et al 2002).…”
Section: Figurementioning
confidence: 99%
“…In the previous study, we examined water and electrolyte metabolism in Tg rats, which is regulated by AVP mainly via V2R in kidney, and showed that there was an adaptive mechanism to prevent water retention caused by sustained hypervasopressinemia (25). Another major action of AVP is vasoconstriction, which is mediated by V1aR in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (25), we successfully restored the downregulation of V2 receptors (V2R) by pretreatment with a V2R antagonist. In the present study, we attempted to restore the downregulation of V1aR by pretreatment with the V1aR antagonist OPC-212168.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation